2022
DOI: 10.1038/s41419-022-04945-z
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-2 promotes Src-mediated tyrosine phosphorylation of androgen receptor and contributes to breast cancer progression

Abstract: Androgen receptor (AR) signaling plays important roles in breast cancer progression. We show here that Kindlin-2, a focal adhesion protein, is critically involved in the promotion of AR signaling and breast cancer progression. Kindlin-2 physically associates with AR and Src through its two neighboring domains, namely F1 and F0 domains, resulting in formation of a Kindlin-2-AR-Src supramolecular complex and consequently facilitating Src-mediated AR Tyr-534 phosphorylation and signaling. Depletion of Kindlin-2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Kindlin-2, a well-known focal adhesion protein, plays a crucial role in regulating integrin-dependent cellular events [23][24][25][26][27][28][29]. Recent studies have reported a role for Kindlin-2 precipitates in multiple integrinindependent pathways that modulate a series of cellular functions [30][31][32][33][34][35][36]. Kindlin-2 is essential for maintaining the hemostasis of many tissues and organs, including bone, renal glomerular, heart and smooth muscle [32,[36][37][38][39].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 1 more Smart Citation
“…Kindlin-2, a well-known focal adhesion protein, plays a crucial role in regulating integrin-dependent cellular events [23][24][25][26][27][28][29]. Recent studies have reported a role for Kindlin-2 precipitates in multiple integrinindependent pathways that modulate a series of cellular functions [30][31][32][33][34][35][36]. Kindlin-2 is essential for maintaining the hemostasis of many tissues and organs, including bone, renal glomerular, heart and smooth muscle [32,[36][37][38][39].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Kindlin-2 is essential for maintaining the hemostasis of many tissues and organs, including bone, renal glomerular, heart and smooth muscle [32,[36][37][38][39]. Kindlin-2 has been reported to be overexpressed in various cancers and depletion of Kindlin-2 effectively suppressed tumor progression [33,34,[40][41][42]. However, to date, it is not clear whether Kindlin-2 plays a role in pancreatic cancer development in vivo and if so, the underlying mechanisms remain to be investigated.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Among these substrates, SRC-mediated ER phosphorylation is necessary for ER binding to the estrogen response element and its subsequent dimerization [ 104 , 105 ]. While SRC-mediated AR phosphorylation is required for Kindlin-2-induced BC cell proliferation and migration in vitro and in vivo [ 106 ]. Based on these studies, the combination of endocrine therapy with SRC inhibitors may represent a treatment regimen in these subtypes of BC.…”
Section: Src Kinase-mediated Signaling Transductions In Bcmentioning
confidence: 99%
“…Kindlin-2 regulates the growth and progression of breast cancer tumors by activating CSF-1-mediated macrophage in ltration, thereby promoting metastatic progression [16]. Its involvement extends to regulating tumor growth and progression by enhancing Wnt signaling through complex formation with β-catenin and TCF4, and contributing to Src-mediated tyrosine phosphorylation of androgen receptor [19] [20]. Therefore, Kindlin-2 has been established a major regulator of several hallmarks of cancer [21].…”
mentioning
confidence: 99%